Thermal insulation of CMAS (Calcium-Magnesium-Alumino-Silicates)- attacked plasma-sprayed thermal barrier coatings. Issue 5 (May 2020) - Boissonnet, G.; Chalk, C.; Nicholls, J.; Bonnet, G.; Pedraza, F.
Abstract: The impact of the penetration of small quantities of calcium-magnesium-alumino- silicates (CMAS) glassy melt in the porous plasma-sprayed (PS) thermal barrier coatings (TBCs) is often neglected even though it might play a non-negligible role on the sintering and hence on the thermal insulation potential of TBCs. In this study, the sintering potential of small CMAS deposits (from 0.25–3 mg.cm −2 ) on freestanding yttria-stabilized zirconia (YSZ) PS TBCs annealed at 1250 °C for 1 h was investigated. The results showed a gradual in-depth sintering with increasing CMAS deposits. This sintering was concomitant with local transformations of the tetragonal YSZ and resulted in an increase in the thermal diffusivity of the coatings that reached a maximum of ∼110 % for the fully penetrated coating.